Microstructure development, mechanical and tribological properties of a semisolid A356/xSiCp composite - Ghandvar, H. (Universidad Nacional Autonoma de Mexico, Centro de Ciencias Aplicadas y Desarrollo Tecnologico, 2017)
This paper presents the results of experimental investigation on microstructure (size and morphology of eutectic Si), impact toughness and sliding wear properties of A356 Al-Si alloy and composites containing 10, 20 and 25 wt% of SiCp reinforcement produced by semisolid stirring technique. The results revealed that an increase in SiCp content leads to a reduction in the size of eutectic Si and also changes its morphology from plate-like to equiaxed. Furthermore, addition of 10 and 20 wt% silicon carbide reinforcement decreased the impact toughness by 6 and 18%, respectively. A356/25wt%SiCp composite registered the lowest impact toughness with reduction of 33% due to debonding and agglomeration of SiCp in the matrix. The sliding wear results showed that the wear resistance of the composites was significantly higher than that of the matrix alloy due to the increase in hardness as well as reduction in the size and also morphology transformation of eutectic silicon with increase in SiCp content. However, the existence of particle-porosity clustering with increasing the SiCp content to 25 wt% played a significant role in deteriorating the wear behavior of the composite.